Clinical Approaches to Hospital Medicine Advances, Updates and Controversies (Springer International Publishing, 2018)
This book provides an update on recent clinical practice and an in-depth view of selected topics relevant to hospital medicine. It is divided into four sections that explore clinical, administrative, systems and ethical issues. Each section places an emphasis on the opportunities, challenges and potential directions of this bourgeoning subspecialty. An important topic covered extensively is how hospitalists are being called to lead on the current opioid epidemic, given that they are well-suited in responding to complicated challenges crossing all specialties. Other chapters explore worldwide practice patterns and practical application of philosophical tools in daily practice. This up-to-date resource provides hospitalists, advanced nurse practitioners, medical students and administrators with the latest research, trends and issues in hospital medicine. .